Optimizing Family and School Partnership in Managing Learners' Behavioural Problems in a Full-Service School Setting - Mekgwe, Tumelo; Maseko, Nonhlanhla; Sedibe, Mabatho (Studies in Learning and Teaching, 2025)
ersistent learners’ behavioural problems in many schools disrupt the teaching and learning process. Every learner has specific demands, and when those needs aren't met at a given point in the educational process, children start acting strangely. This qualitative study explored strategies that families and teachers can employ to manage learners’ behavioural problems in schools in the North West Province. The study was underpinned by Bronfenbrenner's ecological model and the Ubuntu theory. The data were extracted through semi-structured interviews, focus group interviews, and document analysis from twenty-four purposively sampled parents and teachers from two full-service schools. The data were analyzed thematically. Ethical considerations maintained during the investigation include maintaining participants’ confidentiality, obtaining informed consent, ensuring anonymity, and promoting voluntary participation. The findings of this study indicated that effective school and family partnerships are crucial in managing learners’ behavioural problems. Furthermore, the findings reveal that some parents and teachers outlined a welcoming environment, training, consistent communication, and partnership values as strategies that can be adopted to ensure effective family and school partnerships in managing learners' behavioural problems. It was thrilling that both parents and teachers committed to effectively partnering and being agents of change in the development of learners so that they become responsible citizens. This study concludes that the realization of effective family and school partnerships depends on identifying and implementing Ubuntu principles of respect and care. This study also provides a model that is practically usable in inclusive educational settings and contextually grounded, since it uniquely examines how families and full-service schools might optimize their collaborative efforts in managing learners’ behavioural problems.